Road infrastructure spillovers on the manufacturing sector in Mexico - Duran-Fernandez, R; Santos, G (Elsevier, 2014)
This paper investigates the effects of road infrastructure on industrial activity in Mexico from a quantitative perspective. It addresses three main issues. First, it investigates the existence of a relationship between road infrastructure and the industrial average product of labour. Second, it studies the determinants of such a relationship and quantifies the magnitude of the impact of road infrastructure on the average product of labour. Third, it analyses the spatial effects of road infrastructure in Mexico. The findings can be summarised as follows. First, road infrastructure has a positive and significant effect on the industrial average product of labour. However, not all the elements (roads or groups of roads) of the road system have the same effect. Second, we find that the actual magnitude of the effects of accessibility on the average product of labour depends on the physical attributes of the roads, as well as the peculiarities of the road network. Finally, we show that the regional gaps in the average product of labour across the country can be partially attributed to differences in infrastructure endowments. From a methodological perspective, the main contribution of this paper is the development of a comprehensive methodology for the analysis of some of the benefits of road infrastructure in Mexico. This methodology can be applied as a tool in the planning, implementation, and evaluation of actual infrastructure policy in this country.